2010
DOI: 10.1021/jm101346r
|View full text |Cite
|
Sign up to set email alerts
|

Phthalazinone Pyrazoles as Potent, Selective, and Orally Bioavailable Inhibitors of Aurora-A Kinase

Abstract: The inhibition of Aurora kinases in order to arrest mitosis and subsequently inhibit tumor growth via apoptosis of proliferating cells has generated significant discussion within the literature. We report a novel class of Aurora kinase inhibitors based upon a phthalazinone pyrazole scaffold. The development of the phthalazinone template resulted in a potent Aurora-A selective series of compounds (typically >1000-fold selectivity over Aurora-B) that display good pharmacological profiles with significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…A series of 4-substituted-2H-phthalazin-1-ones have been investigated as potent orally bioavailable PARP (poly (adenosine diphosphate-ribose) polymerases) inhibitor [19][20][21][22][23][24][25][26] Olaparib I, MRU-868 II and KU0058958 III are the most interesting PARP inhibitors based on the 4-substituted-2H-phthalazin-1-one scaffold and compound IV inhibits aurora-A kinase based upon a 4-(pyrazole-3ylamino)phenyl-2H-phthalazin-1-one scaffold and has in vitro cytotoxic activity against HCT116 colon cell line 27 , these commercial phthalazinone derivatives are shown in figure 1 . We will present new compound designs from N-substituted phthalazin-1-one derivatives based on the 4-benzylphthalazin-1-one scaffold in an attempt to obtain a potent anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…A series of 4-substituted-2H-phthalazin-1-ones have been investigated as potent orally bioavailable PARP (poly (adenosine diphosphate-ribose) polymerases) inhibitor [19][20][21][22][23][24][25][26] Olaparib I, MRU-868 II and KU0058958 III are the most interesting PARP inhibitors based on the 4-substituted-2H-phthalazin-1-one scaffold and compound IV inhibits aurora-A kinase based upon a 4-(pyrazole-3ylamino)phenyl-2H-phthalazin-1-one scaffold and has in vitro cytotoxic activity against HCT116 colon cell line 27 , these commercial phthalazinone derivatives are shown in figure 1 . We will present new compound designs from N-substituted phthalazin-1-one derivatives based on the 4-benzylphthalazin-1-one scaffold in an attempt to obtain a potent anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…In particular,w ed esigneda nd synthesized as mall series of furopyridazinone-based molecules. The pyridazinone nucleusw as selected because it is present in a plethora of compounds endowed with variousbiologicalactivities (antihypertensive, antithrombotic, anti-inflammatory,a nd anticancer), [16,17] and it is considered ap rivileged structure that is currently experiencingarenewed interest in medicinal chemistry.S tartingf rom this nucleus, we recently presented an expeditiousm ulticomponent one-potr eaction methodology for generating as mall collection of fully substituted furo[2,3d]pyridazin-4(5H)-ones (FPs). [18,19] The facile and efficient synthetic route for the FP derivatives is shown in Scheme 1.…”
mentioning
confidence: 99%
“…Interestingly, Prime et al 28) have reported a novel class of potent, selective, and orally bioavailable inhibitors of aurora-A kinase based upon a 4-(pyrazole-3-ylamino) phenyl-2H-phthalazin-1-one scaffold. Compound (IV) inhibits aurora-A with IC 50 of 71 nM, also, it showed in vitro cytotoxic activity against HCT116 colon cell line with IC 50 of 5.44 nM.…”
mentioning
confidence: 99%